Differential Predictors and Clinical Implications Associated With Long-Term Survivors in IDH Wildtype and Mutant Glioblastoma - Jiang, Haihui; Yu, Kefu; Cui, Yong; Ren, Xiaohui; Li, Mingxiao; Zhang, Guobin; Yang, Chuanwei; Zhao, Xuzhe; Zhu, Qinghui; Lin, Song (Frontiers in Oncology, 2021)
Background Glioblastoma (GBM) is the most aggressive intracranial tumor which can be divided into two subtypes based on status of isocitrate dehydrogenase (IDH). A small fraction of patients after receiving standard treatment can be long-term survivors (LTS). This study was designed to disclose the predictors and clinical implications associated with LTS in IDH wildtype and mutant GBM. Methods Patients who survived beyond five years after diagnosis of GBM were defined as LTS, while those with a survival less than one year were defined as short-term survivors (STS). A total of 211 patients with diagnosis of GBM in Beijing Tiantan Hospital from January 2007 to January 2015 were enrolled, including 44 (20.9%) LTS and 167 (79.1%) STS. The clinical, radiological and molecular features between groups were systematically compared. Results Compared with STS, LTS were a subgroup of patients with a younger age at diagnosis (P=0.006), a higher KPS score (P=0.011), higher rates of cystic change (P=0.037), O6-methylguanine-DNA methyltransferase (MGMT) promoter methylation (P=0.007), and IDH mutation (P=0.049), and more likely to have undergone gross total resection (P<0.001). Survival analysis demonstrated that LTS with wildtype IDH conferred a longer progression-free survival (66.0 vs. 27.0 months, P=0.04), but a shorter post-progression survival (46.5 months vs. not reached, P=0.0001) than those of LTS with mutant IDH. LTS with mutant IDH showed a trend towards increased survival after receiving re-operation (P=0.155) and reirradiation (P=0.127), while this clinical benefit disappeared in the subset of LTS with wildtype IDH (P>0.05). Conclusion The prognostic value and therapeutic implications associated with LTS in GBM population significantly differed on the basis of IDH status. Our findings provide a new approach for physicians to better understand the two subtypes of GBM, which may assist in making more tailored treatment decisions for patients.